2012
DOI: 10.1007/s00122-012-1814-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the barley bract suppression gene Trd1

Abstract: A typical barley (Hordeum vulgare) floret consists of reproductive organs three stamens and a pistil, and non-reproductive organs-lodicules and two floral bracts, abaxial called 'lemma' and adaxial 'palea'. The floret is subtended by two additional bracts called outer or empty glumes. Together these organs form the basic structural unit of the grass inflorescence, a spikelet. There are commonly three spikelets at each rachis (floral stem of the barley spike) node, one central and two lateral spikelets. Rare na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
(52 reference statements)
1
29
0
Order By: Relevance
“…In the first case, the mutants were induced by identical chemical treatment (brh3.g, brh3.h, and brh3.i), in the second case by different treatments (ari-o.40, ari-o.43, and ari-o.143). In each case, the mutants were induced in the same mutagenesis program, and thus we cannot exclude a mix-up of mutant accessions after the mutagenic treatment as it was suggested earlier for alleles of barley loci praematurum-a and third outer glume1 (Houston et al, 2012;Zakhrabekova et al, 2012). Two other cases, however, strongly point toward an independent ancestry of identical mutations.…”
Section: Induced Mutations In Barleymentioning
confidence: 93%
“…In the first case, the mutants were induced by identical chemical treatment (brh3.g, brh3.h, and brh3.i), in the second case by different treatments (ari-o.40, ari-o.43, and ari-o.143). In each case, the mutants were induced in the same mutagenesis program, and thus we cannot exclude a mix-up of mutant accessions after the mutagenic treatment as it was suggested earlier for alleles of barley loci praematurum-a and third outer glume1 (Houston et al, 2012;Zakhrabekova et al, 2012). Two other cases, however, strongly point toward an independent ancestry of identical mutations.…”
Section: Induced Mutations In Barleymentioning
confidence: 93%
“…MLOC_81350 and MLOC_43830 were sequenced in the lines detailed in Dataset S1 exactly as described in Houston et al (8). Sequences were aligned using Geneious version 6.1.2 (Biomatters).…”
Section: Bowmanmentioning
confidence: 99%
“…Spikes were harvested from WT and Zeo1.b plants at 12,18,22,26,31, and 36 dpg. Tissue was fixed and processed for scanning electron microscopy as described previously (8).…”
Section: Bowmanmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes controlling barley inflorescence architecture and development have only been revealed for a few characters. Major genes that control row type (vrs1 [Komatsuda et al, 2007], intermedium-c [Ramsay et al, 2011], and vrs4 [Koppolu et al, 2013]), the conversion of awns into an extra floret (Hooded; Müller et al, 1995), adherence of the hull to the caryopsis (nud; Taketa et al, 2008), swelling of lodicules conferring open/ closed flowering (cleistogamy/chasmogamy) and spike density (cly1 [Nair et al, 2010] and zeo1 [Houston et al, 2013]), elongation of awns and pistil morphology (lks2; Yuo et al, 2012), suppression of bracts (trd1; Whipple et al, 2010;Houston et al, 2012), spike branching (com2; Poursarebani et al, 2015), and brittleness of the rachis (btr1/btr2; Pourkheirandish et al, 2015) were recently cloned. A large number of additional morphological mutants that influence barley inflorescence development (Forster et al, 2007) also have been described, and the underlying genes need to be identified to reach a more complete understanding of the regulatory pathways controlling barley spike architecture and development (Forster et al, 2007).…”
mentioning
confidence: 99%